PERSEBARAN TERUMBU KARANG DI WILAYAH PERAIRAN KARAWANG - Fadhli, Rafdi; Pin, Tjiong Giok (Jurnal Geografi Lingkungan Tropik (Journal of Geography of Tropical Environments), 2018)
Coral reefs are one of the most important marine resource potentials in Indonesia. The purpose of this research is to analyze the influence of physical characteristics of waters on the distribution of coral reefs in the Waters of Karawang region in 2001, 2010 and 2017. The method used is field survey and image data processing using the Lyzenga algorithm to determine the distribution of coral reefs in the Waters of Karawang. The results showed that the physical characteristics of these waters affected the distribution of coral reefs in the long term which in the year 2001 - 2017, because when the physical characteristics of the waters are not in accordance with the quality standards, coral reefs do not die immediately but will undergo various processes until it dies. Temperature measurement does not affect the spread of coral reefs in the Karawang region because at temperatures that are suitable for air quality for coral reefs, coral reefs cannot live in the Karawang region. Whereas in high salinity beyond the standard threshold value, coral reefs cannot grow and develop. In ocean surface currents, live coral reefs are ready to have a pattern that is in the same direction as the average direction of ocean currents in the initial time.